Методика теплового расчёта контактного газокапельного утилизатора теплоты низкотемпературных отходящих газов - Безродный, Михаил Константинович; Рачинский, Артур Юрьевич; Голияд, Николай Никифорович (НТУ "ХПИ", 2016)
Разработана методика расчёта контактного аппарата газокапельного типа для утилизации теплоты низкотемпературных отходящих газов. Для распыления жидкости использовалась механическая центробежная форсунка. Данная методика учитывает реальные условия протекания процессов тепло- и массообмена в системе "конус факела распыливания капель жидкости – сплошная парогазовая среда" и основана на использовании результатов ранее проведённых экспериментальных исследований авторов в указанной системе.

A purpose of this scientific paper is to develop the heat calculation technique for the contact-type heat recovery system of low-temperature effluent gases using mechanical centrifugal nozzles to spray liquid. The calculation technique is based on preliminary experimental investigations carried out by the authors to study nozzle dispersion characteristics and heat-mass exchange processes in the two-phase system: the torch cone used for the dispersion of water drops is the steam-gas mixture and it is also based on the preliminary theoretical analysis of the total interfacial area of interacting phases.
Heat calculation technique for the contact-type gas-drop heat recovery system of low-temperature effluent gases
Keywords: форсунка; парогазовая смесь; ПГС; контактный аппарат; nozzle